Implementasi Algoritme COZMO untuk Enkripsi dan Dekripsi Data pada QR Payment - Suhadak Akbar; Ari Kusyanti; Rakhmadhany Primananda (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2019)
QR payment is a payment method by scanning the QR code from mobile application. QR payment requires a security method so that the transaction data cannot be misused or manipulated by certain parties. Cryptography is one of the techniques that can be used to improve data security. One algorithm that can be used is COZMO algorithm. This algorithm is a stream cipher algorithm formed by a combination of Trivium and A5/1. COZMO algorithm is implemented on two Android applications for customer and cashier using the Java programming language and encrypting the transaction data. Based on the input length during the time performance test, 37 characters took 2.05 seconds, 68 characters required 2.06 seconds, while 169 characters took 2.15 seconds. These results indicated that the number of inputs could affect the processing time. A test was conducted over the input length of 68 characters in order to compare the application's performance time before and after implementing the COZMO algorithm which resulting a time difference of 0.3 seconds on the customer's application and 0.4 seconds on the cashier's application. Statistical calculations of the test results showed significant differences after the COZMO algorithm was applied. On the security test, the ciphertext only attack on ciphertexts could not find any plaintext due to the key used was too long. These results showed that COZMO algorithm could be used to secure transaction data.